KONTRIBUSI HUKUM ISLAM DALAM MEMBANGUN HUKUM NASIONAL BERWAWASAN MULTIKULTURAL - Rossa Ilma Silfiah (Arena Hukum, 2020)
AbstractThe fact that the diversity of laws that develop in Indonesia is strongly infl uenced by the socio-philosophical, socio-political and socio-cultural aspects of the Indonesian people. Legal development, as a function of law, is as a social controller and as a means of social engineering demands that national law be predictive, which is able to predict the workings of the law in the future. Then a multidisciplinary comprehensive study becomes a necessity for the formation of National Law. Legal theories that are developing at the present time are very supportive towards pluralist law. ‘Urf, as a source of law and method, commonly known as al’aadat al-muhakkamah, has been used as a legal basis by the Islamic community in Indonesia together with customary (adat) law. Both are in line to dominate the legal life in Indonesia. When observed directly, most Indonesian people already have their own Scriptures while also obeying existing laws and regulations. Through the method of normative legal research and a comparative approach to law, this research focuses on the synchronization of customary law with Islamic Law, so that it will produce National Law in accordance with the law that lives in society.AbstrakFakta keragaman hukum yang berkembang di Indonesia sangat dipengaruhi oleh sosio-fi losofi k, sosio-politik dan sosio-kultural bangsa Indonesia. Pembangunan hukum, sebagaimana fungsi hukum, yaitu sebagai pengendali sosial (social control) dan sebagai sarana rekayasa sosial (social engineering) menuntut Hukum Nasional menjadi predictiable, yang mampu memerkirakan bekerjanya hukum di masa akan datang. Maka kajian yang komprehensif multidisipliner menjadi kebutuhan bagi terbentuknya Hukum Nasional. Teori-teori hukum yang berkembang mutakhir, sangat mendukung ke arah hukum yang pluralis Urf, sebagai sumber hukum maupun metode, lazim dikenal dengan al’aadat al-muhakkamah, telah dijadikan landasan hukum oleh masyarakat Islam di Indonesia bersamaan dengan Hukum Adat. Keduanya seiring sejalan mendominasi kehidupan hukum di Indonesia. Apabila diamati secara langsung, sebagian besar masyarakat Indonesia telah mempunyai Kitab Suci masing-masing dan mematuhi peraturan perundang-undangan yang ada. Melalui metode penelitian hukum normatif dan pendekatan perbandingan hukum, penelitian ini fokus pada singkronisasi Hukum Adat dengan Hukum Islam, sehingga menghasilkan Hukum Nasional sesuai dengan hukum yang hidup dalam masyarakat.